Study of damage accumulation mechanisms in reinforced aluminum-boron-steel composites during thermal cycling - Vishnyakov, L.R.; Moroz, V.P.; Lavrentyev, V.I. (Functional Materials, 2004)
The internal friction method has been used to study the damage accumulation under thermal cycling of an aluminum-boron-steel composite material produced by hot pressing technique. The steel has been introduced into the material in the form of knitted nets containing different amounts of wires in the bundle. The main mechanism of damage accumulation in the material has been shown to be of binding break-off nature at the aluminum-steel interfaces. Методом внутреннего трения изучается природа накопления повреждений при тер-моциклировании композиционного материала алюминий-бор-сталь, изготовленного методом горячего прессования. Сталь входит в материал в виде трикотажной сетки с различным содержанием проволок в жгуте. Показано, что основным механизмом накопления повреждений в таком композите является нарушение связи на границе алюминий-сталь. Методом внутрішнього тертя вивчається природа накопичення пошкоджень при термоциклюванні композиційного матеріалу алюміній-бор-сталь, виготовленого способом гарячого пресування. Сталь входить в матеріал у вигляді трикотажної сітки з різним вмістом дротиків у джгуті. Показано, що основним механізмом накопичення пошкоджень в цьому композиті є порушення зв’язку на межі алюміній-сталь.